Job Resources and Job Self-Efficacy of Vocational Business Educators: Evidence from Public Universities in Nigeria - Edokpolor, James Edomwonyi; Imeokparia, Patience Osebhakhomen; Asemota, Georgina Okpoa (International Business Education Journal, 2023)
This study’s objective was to learn more about if job resources could predict the vocational business educators’ level of job self-efficacy in public universities in Nigeria. The authors hypothesized that vocational business educators who use different requisite skills, who receive support from colleagues, who experience autonomy in making judgments on jobs, who receive finished feedback on the tasks, who seize the opportunity to acquire requisite skills, and who experience overall job resources are more likely to exert self-efficacy on the job. The quantitative study involved a sample of people, such as vocational business educators (N = 146). Participants completed a structured questionnaire adapted from psychological scales. The results of linear regression analyses indicated that vocational business educators who utilize a variety of skills, receive support from colleagues, receive the freedom to decide on a job, receive feedback on the job done, seize the opportunity to acquire requisite skills, and experience job resources were more likely to exhibit job self-efficacy. The results further suggested that the level of job self-efficacy exerted by vocational business educators is equally predicted by the experiences of job resources. In addition, the results offer some implications for practice.